Arrhythmias in athletes (Cardiac Electrophysiology clinics, 2013)
The book contains the following articles about arrhythmias in athletes: Preface: Arrhythmias in Athletes: From Pathologic Substrates to Life-Saving ShockTherapy - Domenico Corrado, Cristina Basso, and Gaetano Thiene Pathologic Substrates of Sudden Cardiac Death During Sports - Cristina Basso, Elisa Carturan, Kalliopi Pilichou, Stefania Rizzo, Domenico Corrado, and Gaetano Thiene Secondary Prevention of Sudden Death in Athletes: The Essential Role of Automated External Defibrillators - Ashwin L. Rao, IrfanM. Asif, andJonathan A. Drezner Cardiovascular Evaluation of MasterAthletes and Middle-aged/Senior Individuals Engaged in Leisure-time Sport Activities - Mats Bo¨ rjesson and Luc Vanhees Sudden Death in Marathon Runners - JasonJames, AhmedMerghani, and Sanjay Sharma Exercise Testing for Risk Stratification of Ventricular Arrhythmias in the Athlete - Christian Schmied, Corinna Brunckhorst, Firat Duru, and Laurent Haegeli Leisure-time Physical Activity and Sport Participation in Patients with Cardiomyopathies - Antonio Pellicciaand FilippoM. Quattrini ST-Segment Elevation and Sudden Death in the Athlete - Alessandro Zorzi,Mohamed ElMaghawry, FedericoMigliore, Ilaria Rigato, Cristina Basso, Gaetano Thiene, and Domenico Corrado Syncope in the Athlete - Yousef H. Bader andMark S. Link Exercise-Induced Arrhythmogenic Right Ventricular Cardiomyopathy: Seek and You - Andre La Gerche and Hein Heidbuchel Bradyarrhythmias: How Slow Is Too Slow in the Athlete? - Ricardo Stein and Anderson Donelli da Silveira Prevalence and Management of Atrial Fibrillation in Middle-Aged/OlderAthletes - Stefania Sacchi, GiuseppeMascia, Luigi Di Biase, Pasquale Santangeli, John David Burkhardt, Luigi Padeletti, and Andrea Natale Implantable Cardioverter-Defibrillator Therapy in Athletes - Mohamed ElMaghawry, FedericoMigliore, Alessandro Zorzi, Barbara Bauce, Loira Leoni, Emanuele Bertaglia, Sabino Iliceto, and Domenico Corrado